Effect of specimen preparation method on the stress-strain behavior of sand in plane-strain compression tests - Wanatowski, Dariusz; Chu, Jian (ASTM International, 2008)
Experimental results are presented in this paper to study the effect of specimen preparation method on the stress-strain behavior of sand in plane-strain compression tests. The data obtained from K0 consolidation, drained, undrained and strain path tests conducted on medium loose specimens prepared by the moist-tamping (MT) and the water sedimentation (WS) methods are compared. The test data show that the plane-strain compression behavior of medium loose sand under K0, drained and strain-path controlled (including undrained) conditions is affected by the speci- men preparation method. Under K0 conditions, the K0 values obtained from the MT specimens are generally lower than those obtained from the WS specimens. Under drained conditions, more contractive behavior was observed for the MT sand. However, the failure stress ratio (or the failure friction angle) was not affected by the specimen preparation method. The data presented in this paper also illustrate that the compression behavior of medium loose sand in strain-path testing can be affected by the specimen preparation method. However, the differences in the stress-strain behavior will also depend on the strain increment ratio (d v/d 1) imposed on the specimens. In general, different behaviors of the moist-tamped and water- deposited specimens reflect the influence of soil fabrics on the stress-strain behavior of sand.